2014
DOI: 10.7150/ijms.8686
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation Knowledge and Attitudes among Health Science Students in Greece: Emerging Interprofessional Needs

Abstract: Background: The impact of presumed consent on donation rates has been widely debated. In June 2013 Greece adopted a 'soft' presumed consent law for organ and tissue donation, where relatives' approval is sought prior to organ removal.Aims: To report on the knowledge, attitudes and concerns of undergraduate students, enrolled in three health science disciplines, in regards to organ donation and presumed consent.Methods: Undergraduate junior and senior health science students [medical (MS), nursing (NS) and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
5
25
1
8
Order By: Relevance
“…This is similar to the study by Oluyombo et al where only one out of every 4 persons who were willing to be donors, signed the donor card [17]. Symvoulakis in a study conducted with medical care professionals, reported that 8.7% carried a donor card [18]. Figueroa reported that while 80% of the medical students were willing to be donors, 59% were actually registered and signed the donor card [19].…”
Section: Discussionsupporting
confidence: 67%
“…This is similar to the study by Oluyombo et al where only one out of every 4 persons who were willing to be donors, signed the donor card [17]. Symvoulakis in a study conducted with medical care professionals, reported that 8.7% carried a donor card [18]. Figueroa reported that while 80% of the medical students were willing to be donors, 59% were actually registered and signed the donor card [19].…”
Section: Discussionsupporting
confidence: 67%
“…Existen estudios que han reportado el conocimiento y la actitud de estudiantes de medicina acerca de la donación de órganos en universidades extranjeras, con diferente programa académico al utilizado en las universidades públicas de nuestro país 8 . Sin embargo, no se cuenta con estudios de este tipo realizados en México, por lo que el presente trabajo, con más de 3,000 estudiantes, pudiera ser un reflejo de la opinión sobre el tema que los futuros profesionales de la salud tienen en otras entidades federativas o países similares.…”
Section: Discussionunclassified
“…En el presente estudio, el principal motivo para no donar fue miedo a que tomaran sus órganos antes de estar muerto. En otros estudios prevaleció la idea de que la persona debía ser enterrada con sus órganos intactos, o que la donación representaba una mutilación inaceptable 1,4,8,9 . El hecho de que la mitad de los estudiantes que no donarían manifieste temor a que se tomen los órganos antes de estar realmente muerto pareciera demostrar una desconfianza hacia el sistema de salud o una falta de comprensión real del significado de muerte encefálica, es decir, de pérdida de vida equivalente a la «muerte tradicional» por paro cardiorrespiratorio irreversible.…”
Section: Discussionunclassified
See 2 more Smart Citations